Rationale and feasibility of transcatheter pulmonary valve implantation in small conduits with the Edwards Sapien valves. (15th February 2021) - Tengler, Anja; Ulrich, Sarah; Fischer, Marcus; Pastor-Villaescusa, Belén; Kanaan, Majed; Pozza, Robert Dalla; Haas, Nikolaus A.; Jakob, André
Abstract: Background: Conduit dilatation above 110% and TPVI in conduits <16 mm is not recommended. However, if we want to reach normal values for RVOT diameters and diminish reintervention rates, pushing these boundaries is essential. Methods: Analysis of subsequent patients who underwent TPVI with Edwards Sapien valves in conduits ≤16 mm between 2010 and 2020. Results: In n  = 33 cases median age was 13 years (5–20 y) and median weight 47 kg (15–91 kg). Preexisting RVOT grafts were n  = 28 Contegra® conduits and n  = 5 homografts (12 mm n  = 15; 14 mm n  = 11; 16 mm n  = 7). Implanted were the Sapien ( n  = 8), Sapien XT ( n  = 10) and Sapien 3 valve (n = 15) with 20 mm ( n  = 4), 23 mm ( n  = 19), 26 mm ( n  = 9) and 29 mm (n = 1). Mean minimal RVOT diameter after TPVI was 22, 7 ± 2, 3 mm (18–30 mm) which is 150% of the mean minimal RVOT diameter before TPVI (15, 1 ± 4, 3 mm). Covered stents were used in n  = 10 cases. Contained conduit rupture occurred in n  = 7 cases (21%). Residual RVOT gradients of 5, 7 ± 4, 9 mmHg (0–18 mmHg) showed adequate RV unloading. Conclusion: TPVI could be performed successfully in all patients. Dilatation above 150% and a valve/conduit diameter ratio up to 2, 4 were well tolerated. There was a considerable amount of conduit rupture but all were confined without further need for intervention or surgery. Highlights: TPVI with Edwards Sapien valves in conduits and homografts ≤ 16 mm is feasible and safeDilatation of conduits above 150% and a valve/conduit diameter ratio up to 2, 4 were feasible and well tolerated. There was a considerable amount of conduit rupture but all were confined without further need for intervention or surgery. With respect to future valve-in-valve procedures we recommend to aim for the largest possible RVOT diameters.